1999
DOI: 10.1093/jn/129.7.1239
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipids in Food and the Emerging Importance of Sphingolipids to Nutrition

Abstract: Eukaryotic organisms as well as some prokaryotes and viruses contain sphingolipids, which are defined by a common structural feature, i.e. , a "sphingoid base" backbone such as D-erythro-1,3-dihydroxy, 2-aminooctadec-4-ene (sphingosine). The sphingolipids of mammalian tissues, lipoproteins, and milk include ceramides, sphingomyelins, cerebrosides, gangliosides and sulfatides; plants, fungi and yeast have mainly cerebrosides and phosphoinositides. The total amounts of sphingolipids in food vary considerably, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
445
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 519 publications
(462 citation statements)
references
References 165 publications
4
445
0
5
Order By: Relevance
“…It is notable that the GlcCer fraction from ruminants appears to be especially activating for iNKT cells. Ruminant milks are an abundant component of the human diet, and are rich in glycosphingolipids (34). The possibility that dietary lipids might contribute to iNKT cell activation is an exciting one.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that the GlcCer fraction from ruminants appears to be especially activating for iNKT cells. Ruminant milks are an abundant component of the human diet, and are rich in glycosphingolipids (34). The possibility that dietary lipids might contribute to iNKT cell activation is an exciting one.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary sphingolipids, which include sphingomyelin (SM), ceramides, and sphingosine, are mainly found in milk, eggs, and soybeans [12]. It is estimated that the average American consumes 0.3 to 0.4 grams of sphingolipids per day [12]. Sphingomyelin is considered a zoochemical, being present in animal cell membranes but absent from plants [13].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the large concentration of sphingolipids such as sphingomyelin in the plasma membrane, it was held that these molecules only served structural roles. However, over the past few decades, many studies have demonstrated that these molecules, notably ceramide and sphingosine-1-phosphate (S1P), play integral roles in mediating varied cellular processes (Hannun and Obeid, 2002;Igarashi et al, 2003;Merrill Jr. et al, 1997;Spiegel and Milstien, 2002;Spiegel and Milstien, 2003;Strasberg and Callahan, 1988;Tilly and Kolesnick, 2002;Vesper et al, 1999). Ceramide is a second messenger for events as diverse as differentiation, senescence, proliferation, cell cycle arrest, and apoptosis (Hannun, 1994;Hannun et al, 2001;Kolesnick, 2002).…”
mentioning
confidence: 99%